KEGIATAN YASINAN DAN WAQIAHAN DALAM PEMBENTUKAN KECERDASAN SPIRITUAL SISWA DI MTS. MAMBAUL ‘ULUM GEDANGAN - Nurul Aini, Hasan Bisri, Agus Salim, Mohammad Fadil (PRODI PAI FIK UNIRA MALANG, 2023)
This research is motivated by social changes that affect a person's attitudes and behavior. This is because the progress that occurs is not matched by spiritual intelligence. Spiritual intelligence is intelligence that must be possessed by every religious human being, especially for a Muslim. The steps for MTs. Mambaul 'Ulum Gedangan in the formation of students' spiritual intelligence by inviting students to carry out religious activities in the form of Yasinan and Waqiahan. The success achieved in the formation of students' spiritual intelligence is seen from the point of view of religious spiritual, socio-religious, and religious ethics in a good view.. This study aims to explain the formation of students' spiritual intelligence in MTs. Mambaul 'Ulum Gedangan, To explain the Implementation of Yasin and Al-Waqiah Reading Activities in MTs. Mambaul 'Ulum Gedangan, To find out what are the Supporting and Inhibiting Factors of Yasin and Al-Waqiah Reading Activities in MTs. Mambaul 'Ulum Gedangan.